The lived experience of the home educator - Williams, Janice D. (2019)
This qualitative study examines the experiences of twelve home educators from the North Carolina, USA. The primary data collection method was semi-structured interviews, supplemented by visual collages which were completed by participants. Data were coded and analysed using NVivo 12 software. The research resulted in nine major themes which emerged out of the experiences shared by the participants: 1) Structure, 2) Curriculum, 3) Personal Fulfilment, 4) Personal Struggles, 5) Sought Advantages), 6) Reasons for Home Educating, 7) Reflection, 8) Support, and 9) The Decision to Homeschool. I analysed these themes from the participants’ experiences through the lens of inductive thematic analysis. The experiences associated with the home educators in this study serve as a framework for discussion of the way in which home education is experienced by its practitioners and the perceived value home education has in their lives. The research revealed that control is a fundamental necessity for home educators. Additionally, the findings reveal that home educators craft the lifestyle and practice of home education to match their own capacity, desire and lifestyle. Recommendations are made for home educators, traditional educators and further study.